First report of grapevine virus E infecting grapevine in Argentina - Debat, Humberto Julio; Zavallo, Diego; Luna, Facundo; Moyano, Sabrina Noé; Asurmendi, Sebastian; Gomez Talquenca, Sebastian (Springer, 2019)
To investigate the occurrence of GVE in Argentina, a survey was conducted in grapevines from three regions (Mendoza’s North Oasis, East Zone and Uco Valley) of Mendoza province, Argentina, during the 2017/2018 season. A total of 187 plants were screened, including Vitis vinifera Malbec, Cot, Cabernet franc, Cereza, Aspirant Bouchet, Chardonnay, Flame and Paulsen 1103 rootstock (V. berlandieri cv. Rességuier x V. rupestris cv. Lot).